A New Method for Automatic Vehicle License Plate Detection - Corneto, G. L.; Silva, F. A.; Pereira, D. R.; Almeida, L. L.; Artero, A. O.; Papa, J. P.; De Albuquerque, V. H.C. [UNESP]; Sapia, H. M. (Institute of Electrical and Electronics Engineers (IEEE), 2017)
License plate recognition has been widely studied, and the advance in image capture technology helps enhance or create new methods to achieve this objective. In this work is presented a method for real time detection and segmentation of car license plates based on image analyzing and processing techniques. The results show that the computational cost and accuracy rate considering the proposed approach are acceptable to real time applications, with an execution time under 1 second. The proposed method was validated using two datasets (A and B). It was obtained over 92% detection success for dataset A, 88% in digit segmentation for datasets A and B, and 95% digits classification accuracy rate for dataset B.
Keywords: Digits segmentation; Image Processing; License plate detection; OCR; Vehicle License Plate